In Situ TEM Study on Conversion‐Type Electrodes for Rechargeable Ion Batteries. Issue 6 (23rd June 2020) - Cui, Jiang; Zheng, Hongkui; He, Kai
Abstract: Conversion‐type materials have been considered as potentially high‐energy‐density alternatives to commercially dominant intercalation‐based electrodes for rechargeable ion batteries and have attracted tremendous research effort to meet the performance for viable energy‐storage technologies. In situ transmission electron microscopy (TEM) has been extensively employed to provide mechanistic insights into understanding the behavior of battery materials. Noticeably, a great portion of previous in situ TEM studies has been focused on conversion‐type materials, but a dedicated review for this group of materials is missing in the literature. Herein, recent developments of in situ TEM techniques for investigation of dynamic phase transformation and associated structural, morphological, and chemical evolutions during conversion reactions with alkali ions in secondary batteries are comprehensively summarized. The materials of interest broadly cover metal oxides, chalcogenides, fluorides, phosphides, nitrides, and silicates with specific emphasis on spinel metal oxides and recently emerged 2D metal chalcogenides. Special focus is placed on the scientific findings that are uniquely obtained by in situ TEM to address fundamental questions and practical issues regarding phase transformation, structural evolution, electrochemical redox, reaction mechanism, kinetics, and degradation. Critical challenges and perspectives are discussed for advancing new knowledge that can bridge the gap between prototype materials and real‐world applications. Abstract : In situ transmission electron microscopy is a powerful tool to study rechargeable battery materials, providing mechanistic insights into understanding phase transformation and associated structural and chemical evolution upon charge and discharge. The recent progress on reaction mechanism, kinetics, and degradation of conversion‐type electrode materials, especially metal oxides and chalcogenides, is systematically reviewed; the challenges and prospects are also discussed.